BIOLOGICAL ASPECTS OF BANANA SHRIMP (Penaeus Merguiensis DE HANN) IN THE PEMANGKAT WATERS, WEST BORNEO - Duranta Diandria Kembaren (Widyariset, 2013)
Continuous fishing can threat the sustainability of shrimp resources. Studying of biological aspects can be used as a basic knowledge to manage shrimp responsible fisheries. Research about biological aspects of banana shrimp (Penaeus merguiensis) was conducted on April to December 2011 in Pemangkat waters, Sambas district. Data were collected from the fisherman landed in Pemangkat fishing port. Composition of male and female were an unequal in sex ratio. The shrimps was dominated by the size of 23 to 25 mm on carapace length. Individually, female carapace length was 30% longer than male. The growth characteristic was isometric in male and female. Spawning occurred all year around, and reach its peak on November. Carapace length at first capture of banana shrimp was 23,75 mm and carapace length at first maturity was 33,67 mm. Fishing pressure at this water was high and the capture dominated by the young shrimp. This condition threat the sustainability of shrimp fisheries.